Analisis Pengaruh Perilaku Manajemen Waktu terhadap Prestasi Akademik Mahasiswa - Kamilatunnisa Kamilatunnisa; Kasih Kasih; Sonya Anggun Oktoviani; Sri Mulyeni (Lembag, 2025)
Time management is a key non-cognitive competency that supports students’ learning autonomy and academic achievement in competitive higher education settings. This study aimed to examine the influence of time management behavior on academic performance. Using a quantitative correlational design, the research involved 50 second-semester students from the Faculty of Economics at Universitas Nasional Pasim Bandung. Data were collected through a closed-ended questionnaire based on a five-point Likert scale and analyzed using simple linear regression. The results indicated a positive and significant influence, as shown by the regression equation Y = 10.742 + 0.844X and a coefficient of determination R² = 0.505. These findings underscore the role of time management as a robust predictor of academic success, highlighting the need for universities to incorporate structured time management training into student soft skills development programs.